Pengembangan Model Pembelajaran REQUEST (Resume, Question, Investigation, Solution and Presentation) dalam Pembelajaran IPA - Jiniari Dewi Dewi; Suratno Suratno; Iis Nur Asyiah (Program Studi Magister Pendidikan IPA FKIP Universitas Jember Bekerjasama dengan Perkumpulan Pendidik IPA Indonesia (PPII), 2016)
The innovation of curriculum field requires teachers to change the learning system of teacher centered become student centered. Therefore developing REQUEST learning model is necessary to develop students' activities during the learning process. The study refers to Borg and Gall development model. Validity, practicability and effectiveness of the REQUEST learning model obtained from the validation sheet and questionnaire. Validity and responses from the teachers and students changed to percentage then converted to descriptive qualitative data using the assessment criteria of validity. The results showed that REQUEST learning model has been valid with the validity value 80,77% and also supported by positive response from the teacher and students after using REQUEST learning model. REQUEST learning model consists of four stages, which is preparing a summary, find problems that are arranged in a questions, conducting investigations, and finding solutions to solve the problems then to be presented in front of the class.